Beyond Bloom's Taxonomy: Integrating "searching as learning" and e‐learning research perspectives. Issue 1 (1st February 2019) - Reynolds, Rebecca; Meyers, Eric; Ghosh, Souvick; Novin, Alamir
ABSTRACT: Searching as learning work is growing in interest, however definitions of 'learning' in this space have been somewhat narrow. Here we propose a panel sponsored by SIG InfoLearn that will feature presentations from three scholars whose work falls in the domain of "searching as learning, " followed by a synthesis presented by a fourth scholar along with one of the panelists, who will draw key conceptual intersections among the three empirical research papers and then explicate linkages to existing research in the learning sciences that has potential to further inform the ongoing development of the panelists' and others' work in this domain.